The new Unimore interdisciplinary teaching on transversal sustainability skills - Grazia Ghermandi; Francesca Despini (Universitas Diponegoro, 2022)
The global situation of the Covid-19 pandemic has changed several aspects of University life and management. In this context, the University of Modena and Reggio Emilia (Unimore) has introduced a new course for all of its students called